2001
DOI: 10.1006/cbir.2001.0769
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Downregulates the Number of Caveolae and the Level of Caveolin in Uterine Smooth Muscle

Abstract: Estrogen and progesterone, while regulating uterine functions, also regulate the number of caveolae and the level of caveolin. Large numbers of caveolae, as well as elevated expression of caveolin-1 and caveolin-2 isoforms in the myometrium of ovariectomised (OVX) rats were detected. 17beta-estradiol (E2) has a downregulating effect: the treatment of OVX rats with E2 (5 microg/animal) reduced the formation of caveolae by approx. 90%. Western blots clearly demonstrated the reduction of membrane caveolin-1 and -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 41 publications
3
41
1
Order By: Relevance
“…It is possible that this complex influences PI3K/Akt activity. In vivo, estrogen decreases the number of caveolae in uterine smooth muscle, an effect that was blocked by ICI 182 780 [60]. In support of a relationship between E 2 and caveolin, E 2 differently influenced caveolin production in MCF-7 cells and VSMCs [56].…”
Section: Estrogen Coupling To Enos Might Involvementioning
confidence: 88%
“…It is possible that this complex influences PI3K/Akt activity. In vivo, estrogen decreases the number of caveolae in uterine smooth muscle, an effect that was blocked by ICI 182 780 [60]. In support of a relationship between E 2 and caveolin, E 2 differently influenced caveolin production in MCF-7 cells and VSMCs [56].…”
Section: Estrogen Coupling To Enos Might Involvementioning
confidence: 88%
“…Recently, studies of the regulation of receptor signaling in endothelial caveolae have suggested their role as calcium sensors . Caveolae are richly expressed in smooth muscles, including myometrium (Kwan et al, 1986), and their numbers are regulated (Turi et al, 2001). Perhaps the conundrum presented here can be resolved on the basis of the organization of receptor signaling in myometrium between detergent-insoluble glycolipid-rich domains, including rafts and caveolae (Anderson and Jacobson, 2002), and the soluble and myo-filamentous regions of the cell.…”
Section: Caveolar Signalingmentioning
confidence: 89%
“…The gene for caveolin 2 (CAV2) was up-regulated by ATF2; caveolin expression in the myometrium of the pregnant rat is known to be suppressed in the first half of pregnancy, after which it increases up to delivery, increasing the number of caveolae present in myometrial cells (Turi et al 2001). This has been shown to be dependent upon levels of oestrogen and progesterone.…”
Section: Discussionmentioning
confidence: 99%